Analysis Of Themes and Trends in Life Sciences and Biomedical Research Virtual Reality - Sahibu, Supriadi; Munsyir, Mulawarman; Gani, Hamdan; Taufik, Imran; Iskandar, Akbar (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2022)
The purpose of this study was to investigate the theme of the abstract, the theme of the Title on Virtual Reality in the Sciences and Biomedical Sciences and to investigate the trends of authors and countries who are major contributors to research on virtual reality in the sciences and biomedical sciences, the researchers used metadata from 497 journals. scientifically indexed with topic modeling algorithms. The results of the study found that for virtual reality themes listed in the abstracts of science and biomedical fields, the words that often appear were study and systems related to pediatric surgery, stroke and cancer. Then the research theme in the virtual reality title regarding science and biomedicine is to get words that often appear, namely evaluation and videos that contain about the fields of dental health, stroke and cancer, Furthermore, from a technological point of view, it relates to head-mounted devices to display 2 or 3 dimensions, and educational psychometric technology relates to learning to care for children for students. While the sports side is related to the movement of the body's physical activity in adults. Analysis of research trends for authors and countries that are major contributors to virtual reality research on science and biomedical based on wordcloud analysis with names that often appear in virtual reality is Wiederhold BK and the dominant country is United State.